Canakinumab as rescue therapy in familial Mediterranean fever refractory to conventional treatment - Alpa M; Roccatello D (Dove Medical Press, 2015)
Mirella Alpa, Dario Roccatello Centro di Ricerche di Immunopatologia e Documentazione su Malattie Rare (CMID), Struttura Complessa Direzione Universitaria di Immunologia Clinica, Università di Torino e Ospedale G Bosco, Torino, ItalyAbstract: Familial Mediterranean fever is an autosomal recessive autoinflammatory disorder mainly affecting Mediterranean populations, which is associated with mutations of the MEFV gene that encodes pyrin. Functional studies suggest that pyrin is implicated in the maturation and secretion of interleukin-1 (IL-1). The IL-1 receptor antagonist or anti-IL-1 monoclonal antibody may therefore represent a rational approach for the treatment of the rare patients who are refractory to conventional therapy. We report the case of a young female affected by familial Mediterranean fever who proved to be resistant to colchicine and was successfully treated with canakinumab.Keyword: interleukin-1, colchicine, familial Mediterranean fever, anti-IL-1 treatment, biologic agents